2014
DOI: 10.29252/jnkums.5.4.785
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of lifestyle and hypertension in administrative employees in Bojnurd rural areas

Abstract: Background and Objectives: Life style is composed of a chain of active parameters in all dimensions of human life and has a substantial impression on health of population. Since vast majority of health problems has a strong relationship to life style, occurrence of many somatic and psychological disorders would be prevented provided that life style rectified. Blood pressure is one of the most important health criteria moderated when life style has been changed. The aim of this investigation was to study the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Type D personality affects the biological causes (e.g. blood pressure, blood lipids, and tobacco use) of coronary heart disease [22,23,29]. In the present research, the mean scores of stress control and interpersonal relationships and support were 13.27 and 17.27, respectively, which gained lower scores compared with the mean scores of the other dimensions of health-promoting lifestyle.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Type D personality affects the biological causes (e.g. blood pressure, blood lipids, and tobacco use) of coronary heart disease [22,23,29]. In the present research, the mean scores of stress control and interpersonal relationships and support were 13.27 and 17.27, respectively, which gained lower scores compared with the mean scores of the other dimensions of health-promoting lifestyle.…”
Section: Discussioncontrasting
confidence: 50%
“…Investigating the predictive role of type D personality and health-promoting lifestyle in predicting cardiac function in patients with acute myocardial infarction also showed a correlation coefficient of 0.039 and 0.18 in patients with acute myocardial infarction. In addition, the indirect effect of type D personality variable on the cardiac function of patients with acute myocardial infarction with mediating the health-promoting lifestyle explained variance (R 2 ) as much as 0.37, indicating an indirect effect on the cardiac function [20,22,23,38,39]. The results were also consistent with the Sedaghat et alStein et aland Mirzaie et al study results which reported that following a promoting lifestyle, especially in cardiac patients, is not only being aware of a healthy lifestyle but is also being influenced by psychological factors such as personality type and motivation [19,24,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate the need for effective interventions to change lifestyle in order to control and reduce blood pressure. In Saber Moghadam et al study (2013), inactivity, stress, obesity and poor nutrition mentioned as the most important factors affecting the incidence of hypertension ( 20 ). In Mansourian et al study (2012), a significant relationship was observed between the dimensions of lifestyle (physical activity, nutrition, spiritual growth, interpersonal communication and stress management) and hypertension ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of this disease is increasing in all countries, especially Iran [ 8 , 9 ]. According to the Ministry of Health and Medical Education in Iran, 20 out of every 100 adults have HTN [ 10 ].…”
Section: Introductionmentioning
confidence: 99%